The microsporidian spore invasion tube. IV. Discharge activation begins with pH-triggered Ca2+ influx (The Rockefeller University Press, 1985)
The microsporidian spore extrusion apparatus activates with a calcium influx from Spraguea lophii spore wall/plasma membrane; this influx requires preconditioning with an extrasporular shift in medium pH to the alkaline in the presence of the polyanions mucin or polyglutamate. Undischarged S. lophii spores display calcium bound to the wall/plasma membrane with a characteristic calcium-chlorotetracycline fluorescence; this fluorescence declines significantly during spore discharge. S. lophii spores do not discharge when spore wall/plasma membrane calcium is removed with EGTA. Extrasporular mucin or polyglutamate and a pH shift to the alkaline appear to be necessary preconditions for the triggering of the influx of spore wall/plasma membrane-bound 45Ca2+. Ionophore A-23187 also effectively activates spore discharge without other extrasporular polyanions. Micromolar concentrations of the calcium antagonists lanthanum or verapamil prevent spore discharge, and micromolar concentrations of calmodulin inhibitors chlorpromazine and trifluroperazine prevent spore discharge. Calmodulin, visualized with a calmodulin antibody and a peroxidase conjugate, is localized particularly on the plasma membrane and the polaroplast membranes of the extrusion apparatus.